Beyond the Scale: Investigating Adiponectin, ICAM-1, and VCAM-1 as Metabolic Markers in Obese Adolescents with Metabolic Syndrome - Nur Aisiyah Widjaja; Leonardo Alexander Caesar; Suhasta Nova; Eva Ardianah (Journal of Obesity)
Background. Adiponectin acts to prevent vascular dysfunction due to obesity by inhibiting ICAM-1 and VCAM-1 expressions. Objective. We investigate adiponectin ICAM-1, VCAM-1, and metabolic syndrome (MetS) in obese adolescents. Methods. A cross-sectional study with healthy obese adolescents aged 13 to 18 years was conducted from October 2019 to January 2020. Statistical analysis conducted was a test of normality and homogeneity tests, ANOVA/Kruskal–Wallis, independent sample T-test/Mann–Whitney U test, and Spearman correlation and determined as significant if p value <0.05. Results. 125 obese adolescents were recruited. 42 (33.6%) were obese with MetS (we grouped as MetS) and 83 (66.4%) subjects without MetS (non-MetS group). VCAM-1 was significantly higher on boys with MetS compared to girls with MetS, and even girls with MetS had lower levels of VCAM-1 than boys with non-MetS. ICAM-1 was significantly higher in boys with low-level HDL-c (p<0.05) and correlated weakly with HDL-c, while adiponectin levels were significantly lower in girls with central obesity and hypertriglyceridemia. Path analysis showed that triglyceride had a direct effect on ICAM-1 but not VCAM-1 in both obese boys and girls. Adiponectin had a negative direct effect on ICAM-1 and VCAM-1 in girls. However, on boys, diastole blood pressure had a negative direct effect, which might be the role of sex hormones indirectly. Conclusion. VCAM-1 was significantly higher in boys than girls, which showed that boys had a higher risk of atherosclerosis. ICAM-1 showed no significant difference in both gender and metabolic states. Adiponectin showed a protective effect by lowering ICAM-1 and VCAM-1 directly on girls.